2020
DOI: 10.1101/2020.07.01.182253
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GsERFenhances aluminum tolerance through an ethylene-mediated pathway inArabidopsis thaliana

Abstract: AbstractThe ethylene response factor (ERF) transcription factor is a subfamily of AP2/ERF superfamily in plants, which plays multiple roles in plant growth and development as well as stress response. In this study, we found that the GsERF gene from BW69 line of wild soybean held a constitutive expression pattern and induced by aluminum stress with more transcripts in soybean root. The putative GsERF protein containing an AP2 domain was in the nucleus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Moreover, Chen et al showed that GmGRPL conferred Al tolerance in Arabidopsis through regulation of the level of IAA and ethylene and improvement of antioxidant activity [38]. Similarly, overexpression of the GsERF gene enhanced Al tolerance of Arabidopsis through an ethylene-mediated pathway [156]. In addition, ABA was involved in regulating Al tolerance [157].…”
Section: Plant Hormones Involved In Adaptation To Al Stressmentioning
confidence: 99%
“…Moreover, Chen et al showed that GmGRPL conferred Al tolerance in Arabidopsis through regulation of the level of IAA and ethylene and improvement of antioxidant activity [38]. Similarly, overexpression of the GsERF gene enhanced Al tolerance of Arabidopsis through an ethylene-mediated pathway [156]. In addition, ABA was involved in regulating Al tolerance [157].…”
Section: Plant Hormones Involved In Adaptation To Al Stressmentioning
confidence: 99%